1995
DOI: 10.1021/jm00007a012
|View full text |Cite
|
Sign up to set email alerts
|

Novel Modified Carboxy Terminal Fragments of Neuropeptide Y with High Affinity for Y2-Type Receptors and Potent Functional Antagonism at the Y1-Type Receptor

Abstract: Peptide analogs of neuropeptide Y (NPY) with a Tyr-32 and Leu-34 replacement resulted in the decapeptide TyrIleAsnLeuIleTyrArgLeuArgTyr-NH2 (9; Table 1) and a 3700-fold improvement in affinity at Y2 (rat brain; IC50 = 8.2 +/- 3 nM) receptors when compared to the native NPY(27-36) C-terminal fragment. In addition, compound 9 was an agonist at Y1 (human erythroleukemia (HEL) cell; ED50 = 8.8 +/- 0.5 nM) receptors with potency comparable to that of NPY(1-36) (ED50 = 5 nM). Molecular dynamics and 1H-NMR were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 23 publications
1
67
1
Order By: Relevance
“…21 This peptide has been amenable to conjugation with a variety of radiolabels and fluorophores. In particular, Gueŕin et al showed that the Ileconjugated Lys to incorporate DOTA, NOTA or fluorine moieties, 22,23 and we extended this result to include a rhodamine fluorophore.…”
Section: Figurementioning
confidence: 99%
“…21 This peptide has been amenable to conjugation with a variety of radiolabels and fluorophores. In particular, Gueŕin et al showed that the Ileconjugated Lys to incorporate DOTA, NOTA or fluorine moieties, 22,23 and we extended this result to include a rhodamine fluorophore.…”
Section: Figurementioning
confidence: 99%
“…Therefore, peptide 2 constitutes a promising therapeutic for the management of obesity. (Leban et al, 1995) was purchased from Bachem Biosciences (King of Prussia, PA) (catalog number H-3546). BIIE0246 (Doods et al, 1999) andL-152,804 (Kanatani et al, 2000a) were purchased from Tocris Cookson Inc. (Ellisville, MO) (catalog numbers 1700 and 1382, respectively).…”
Section: 24-triazolidin-4-yl)ethyl]amino]carbonyl]butyl]-1-[2-mentioning
confidence: 99%
“…Endogenous NPY1 and NPY4 receptors were blocked with 1 M (Pro 30 ,Tyr 32 ,Leu 34 )-neuropeptide Y(28-36), and the NPY5 receptor was blocked with 1 M L-152,804 (Leban et al, 1995;Kanatani et al, 2000a). Membrane pellets were suspended in icecold buffer A (50 mM HEPES, pH 7.4, 10 mM CaCl 2 , and 5 mM MgCl 2 ) and immediately used for determining protein content with the Bradford assay (Bio-Rad, Hercules, CA) and for binding assays.…”
Section: Referencementioning
confidence: 99%
“…So far, the 24-mer peptide NPY(13-36) is most frequently used for the testing of Y2 receptor mediated actions [4]. We and others have shown recently that smaller centrally or N-terminally truncated analogs such as [ NPY are full Y2 receptor agonists [9] or show at least good binding properties [12][13][14][15]. In addition, the L-Ala scan of NPY 1-36 suggests that only the C-terminal amino acids are involved in receptor binding and we speculated that the N-terminal residues only serve for the stabilization of the molecule [16].…”
Section: Introductionmentioning
confidence: 99%